COMPARATIVE STUDY OF THE DISEASE KUSTHA IN DIFFERENT AYURVEDIC SAMHITA (International Journal of Food and Nutritional Sciences, 2022)
The skin is the outermost covering of the body which acts as a protective barrier and protects the body from invasion of different micro- organism and other harmful agents of the environment. But very often, it is exposed to many entities which can damage it and may produces many disease including differents types of skin disorders as wellThe primitive knowledge of Ayurveda, had been described very briefly in Vedas and Puranas but later on in Samhita period this knowledge was systematically compiled and Scientifically developed by the great Ayurvedic Acharyas and was made available to the society in the form of Samhitas. Here all the skin diseases have been mentioned under the name Kustha, Ayurveda is the science and art of healing that deals with all aspects of an individual. In Ayurveda, psychological factors have been given equal importance as physical & physiological factors in the etio-pathogenesis of various dermatological disorders.. There are various dietery (aharaja), habitual/regimental factors mentioned in ayurveda which causes dosh and dushya disturbance and produces the Kustha roga. Kustha was described mainly under two category i.e. maha kushtha and kshudra kushtha, which again descried under eight and seventeen type.